0879 Nightmare Recall Rates Correlate with Hyperarousal in Trauma-exposed Individuals. (12th April 2019) - Oliver, Katelyn I; Ulsa, Ma C; Daffre, Carolina; Seo, Jeehye; Moore, Kylie N; Gazecki, Samuel; Lasko, Natasha B; Pace-Schott, Edward F
Abstract: Introduction: Trauma-related nightmares are a distinguishing feature of the "re-experiencing" criteria for posttraumatic stress disorder (PTSD). We examined whether "hyperarousal" criterion features also predict rates of negative dreams in recently traumatized individuals. Methods: Seventy participants aged 18-40 (45 females) exposed to a traumatic event within the past two years completed the Clinician-Administered PTSD Scale (CAPS-5) and the PTSD Checklist for DSM-5 (PCL-5). CAPS-5 scores ranged from 0-50 (mean 21.4, SD 12.8) and 32 met DSM-IV-TR PTSD criteria. All participants completed sleep diaries over 11-27 nights (mean 14.7, SD 2.3) containing questions that asked whether a dream was recalled, whether it was a nightmare (causing awakening) or a bad dream, and resemblance to trauma (exactly, similar, possibly similar, or unrelated). Per-total-diary and per-total-dream percentages for nightmares, bad dreams, and their sum as well as the sum of dreams that were exactly-like/similar to the trauma were calculated. A Composite Hyperarousal Index (CHI) was computed from the hyperarousal items on the CAPS-5, the PCL-5 and a published hyperarousal scale. A Composite Psychopathology Index (CPI) was computed from the Depression, Anxiety and Stress Scale, the WHO Disability Assessment Schedule 2.0 and the Symptom Checklist-90. Results: CHI significantly predicted per-diary nightmare recall rate (R=0, 32, p=0.008), bad dream recall rate (R=0.33, p=0.006), their combined rates (R=0.411, P=0.0007) but not those that were exactly-like/similar-to the trauma (R=0.18, p=0.15). For percentages on a per-dream basis, although CHI didn't predict nightmares alone (R=0.17, p=0.17), it did predict bad dreams (R=0.29, p=0.02), combined nightmares and bad dreams (R=0.41, p=0.0008) and trended for those exactly-like/similar-to the trauma (R=0.24, p=0.059). Relationships of CPI with these dream variables were weaker either on a per-night basis [nightmare rate (p=0.52), bad dream rate (p=0.013), combined rates (p=0.049), and those exactly-like/similar-to (p=0.68)] or a per-dream basis (p=0.51, 0.037, 0.016 and 0.51 respectively). Conclusion: Hyperarousal predicted total bad dreams and nightmares as well as those specifically trauma-related. Their relationship with general psychopathology was weaker. Hyperarousal symptoms may play a role in generating the intrusion symptoms of PTSD over and above levels of general psychopathology. Support (If Any): R01MH109638